Immunomodulatory Activity of Ganyong Tuber (Canna edulis K.) Extract on Phagocytosis, Leukocytes, and Antibody of Mice against Bacterial Infections - Nadyatul Ilma Indah Savira; Siti Shofa Assyifa Qulbi; Meilia Putri Marditianingsih; Mumtahana laili; Erlia Narulita; Manikya Pramudya; Alfan Irsyad Maulana (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights Ganyong tuber exhibits immunomodulatory activity against Staphylococcus aureus infection in mice. Ganyong tuber extract increases phagocytic activity, leukocyte count, and spleen weight in infected mice. ABSTRACT Background: Ganyong tubers (Canna edulis K.) are widely consumed by Indonesians as an alternative food source. However, no studies have investigated the pharmacological properties of ganyong tubers, particularly their immunomodulatory activity. Objective: This study aimed to evaluate the immunomodulatory effects of ganyong tubers in mice infected with Staphylococcus aureus. Material and Method: This study used a randomized experimental design involving 30 male BALB/c mice divided into five groups, including a normal control, a negative control (infected with Staphylococcus aureus), and three groups treated with ganyong (Canna edulis K.) extract at doses of 50, 100, and 150 mg/kg BW. The extract was administered orally for seven days, followed by S. aureus injection. Phagocytic activity, leukocyte count, spleen weight, and antibody levels were evaluated using microscopy and ELISA. Data were analyzed using one-way ANOVA and Duncan’s post hoc test. Result: This study evaluated the immunomodulatory effects of ganyong tuber (Canna edulis K.) extract on phagocytosis activity and capacity, leukocyte count, spleen weight, and antibody levels in mice infected with Staphylococcus aureus. Phagocytosis activity and capacity were highest in the group receiving 50 mg/kg body weight (BW) extract, with decreasing effects at higher doses. Leukocyte counts were highest in the infected untreated group, while spleen weight was significantly increased in the 50 mg/kg BW treatment group compared to controls. Although the 100 mg/kg BW group showed the highest antibody levels, these differences were not statistically significant. Conclusion: Ganyong tuber extract demonstrated immunomodulatory activity by enhancing innate immune responses against S. aureus infection.